Pembuatan Motion Grafis Exam dan Materi di Sekolah Vokasi IPB untuk Media Pembelajaran secara Online - Aep Setiawan (P3M Politeknik Negeri Bengkalis, 2020)
Graphic products are expected to make it easier for lecturers of IPB University Vocational Schools to make exams and materials for online learning. The method used in several stages, including preproduction, production and testing. The motion graphics product that will be made is the steps for making exams and materials in the LMS of the IPB University vocational school in two-dimensional multimedia. The steps for making exams and materials may already have guidelines in writing, but they need to be made in graphic form which is presented in visual form. Making motion graphics requires hardware and software with certain specifications.